Polymer Brushes Tethered ZnO Crystal on Cotton Fiber and the Application on Durable and Washable UV Protective Clothing. Issue 14 (4th June 2019) - Wang, Xi; Chen, Xiaogang; Cowling, Stephen; Wang, Libo; Liu, Xuqing
Abstract: To improve the durability and washability of ultraviolet (UV) protective fabrics, grafted polymer brushes are introduced as platforms for in situ growth of zinc oxide (ZnO) nanostructure on modified cotton fibers, using the electroless deposition approach. Hollow cotton fiber acts as a microreactor for ZnO deposited on both inner and outer surfaces. More importantly, adjusting the reaction in a microenvironment enables effective control of the morphology of ZnO crystals and the functionalized fabric shows durable UV blocking properties. Unlike other finishing processes, the functional ZnO nanocrystals are grown not only on the surface of the fibers but also inside of the hollow cotton fibers, but with a different morphology. This unique property, postmodification allows the functional fabrics to show good antifriction capability, washability, and durability. The combination of zinc oxide and textiles brings out new features for plain cloth, and the final product can be applied to outdoor clothing, protective suits, tents, and curtains, etc. Abstract : Grafted polymer brushes are used as platforms for in situ growth of zinc oxide (ZnO) nanocrystals on cotton fibers by electroless deposition, to fabricate durable and ultraviolet (UV) blocking fabrics.